Ecological Justice-Based Reclamation and Post-Mining Regulations in Indonesia: Legal Uncertainty and Solutions - Wicaksono, Muhammad Bagus Adi; Rahmawati , Wiwit (CV. Ius et Ambientis, 2024)
This study seeks to delineate the reasons that reclamation and post-mining rules in Indonesia now lack a foundation in ecological justice and to propose future regulations that embody ecological justice in post-mining reclamation. This study employs normative legal research through statutory and conceptual methodologies. The findings indicate that the regulatory framework governing reclamation and post-mining responsibilities for coal voids lacks a foundation in ecological justice, as it excludes considerations for non-human and non-living entities within the legal parameters of reclamation and post-mining obligations. The issue begins with the overlapping legal framework and the lack of implementing rules, as well as the procedure for establishing reclamation guarantee funds. The legal framework is suboptimal, and there is no dedicated agency or commission addressing reclamation and post-mining responsibilities. A regulatory framework for the reclamation and post-mining responsibilities of coal voids, grounded in ecological justice, which incorporates considerations for non-human and non-living entities, establishes a dedicated institution to oversee reclamation and post-mining duties in collaboration with the Ministry of Environment and Forestry and the Ministry of Energy and Natural Resources, and introduces mechanisms for reclamation and post-mining guarantees, specifically in the form of non-cash instruments or bonds. Revise the regulatory framework for reclamation and post-mining responsibilities